2021
DOI: 10.3390/info12070280
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effect of Gender on the Relationship between Technology Readiness Index and Consumers’ Continuous Use Intention of Self-Service Restaurant Kiosks

Abstract: This study aims to analyze the moderating effect of gender on the relationship between technology readiness and willingness to continue using self-service kiosks in fast-food restaurants among middle-aged and older consumers. We conducted a survey from 1 May to 30 May 2020 among 320 consumers born in or before 1980 who only used kiosks in fast-food restaurants. The findings are as follows: First, the more innovative and optimistic the consumer, the more they are willing to continue using kiosks, whereas the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…On the other hand, the finding shows that male MSCE examiners had higher propensity for technology than their female counterparts. Na, Lee and Yang (2021) also found that the mean scores of optimism and innovativeness were higher in men than in women, whereas that of discomfort was higher in women than in men. In what would appear as an explanation to this finding, Zagel, Süßmuth and Glomann (2014) established that females show less trust of technology and its associated service.…”
Section: Discussionmentioning
confidence: 73%
“…On the other hand, the finding shows that male MSCE examiners had higher propensity for technology than their female counterparts. Na, Lee and Yang (2021) also found that the mean scores of optimism and innovativeness were higher in men than in women, whereas that of discomfort was higher in women than in men. In what would appear as an explanation to this finding, Zagel, Süßmuth and Glomann (2014) established that females show less trust of technology and its associated service.…”
Section: Discussionmentioning
confidence: 73%
“…Additionally, a study examined the intentions to adopt SST among older consumers, considering chronological and subjective age and the future time perspective [ 9 ]. Another study investigated older consumers’ determinants of self-service kiosk adoption in fast-food restaurants [ 35 , 36 ] or in self-checkouts [ 37 ]. Therefore, prior studies have focused on users’ adoption of technology, differences within the older population’s use of technology, and users’ responses to the use of technology in terms of adoption or barriers.…”
Section: Research Backgroundmentioning
confidence: 99%
“…For instance, Binyamin et al ( 2020 ) examined the moderating role of gender on student acceptance of learning management systems in Saudi Arabia. Likewise, Na et al ( 2021 ) examined the moderating effect of gender on the relationship between technology readiness and consumer intention of self-service in Korea. Merhi et al ( 2021 ) examined the moderating role of gender on consumer intention to use mobile banking in Lebanese and British banks.…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%